Early Cretaceous volcanic-arc magmatism in the Dalat-Kratie Fold Belt of eastern Cambodia: implications for the lithotectonic evolution of the Indochina terrane - Shellnutt, J. Gregory; Ma, George S.-K.; Chan, Jacky S.-L.; Wong, Jean P.-M.; Wang, Kuo-Lung (Frontiers in Earth Science, 2023)
Mesozoic granitic plutons are found throughout the Indochina terrane of eastern Cambodia and southern Vietnam. The granitic rocks range in age from Early Triassic (240 Ma) to Late Cretaceous (80 Ma) and record distinct tectonomagmatic periods associated with subduction of the Paleotethys and Paleo-Pacific oceans. Samples collected from the Snoul pluton, eastern Cambodia are composed of silicic and intermediate dioritic rocks, and basalt. The quartz diorites and diorites are magnesian, metaluminous, calcic to calc-alkalic, and similar to volcanic-arc granitoids whereas the basaltic rocks are compositionally similar to within-plate basalt. Zircon U-Pb geochronology and Lu-Hf isotopes and whole rock Sr-Nd isotopes show that the silicic rocks are Albian and isotopically juvenile (107.5 +/- 0.3 Ma, 109.1 +/- 0.4 Ma; eHf(t) = +7.0-+17.0; 87Sr/86Sri = 0.704313-0.707681; eNd(t) = +3.1-+4.9). Fractional crystallization modeling using a dioritic composition as the parental magma demonstrates that it is possible to generate the quartz diorite compositions under oxidizing (dFMQ +1) and hydrous (H2O = 2 wt%) conditions suggesting that they are consanguineous. The isotopically juvenile nature of the dioritic rocks and their compositional similarity (SiO2  56 wt%, Al2O3 = 15 wt%, Sr = 400 ppm, Y = 18 ppm, Yb = 1.9 ppm) to adakitic rocks indicates that the parental magmas of the Snoul pluton were likely derived by partial melting of juvenile mafic basement rocks of the Indochina terrane. Moreover, Early Cretaceous plutonic rocks of Cambodia are isotopically distinct from plutonic rocks of similar age and tectonic setting from Vietnam suggesting that there could be a lithotectonic domain boundary within the Southern Indochina terrane. In contrast, the basaltic rocks likely record a temporally distinct period of magmatism associated with Late Cenozoic tensional plate stress.